2020
DOI: 10.1016/j.cub.2020.04.085
|View full text |Cite
|
Sign up to set email alerts
|

Arp2/3 and Mena/VASP Require Profilin 1 for Actin Network Assembly at the Leading Edge

Abstract: Cells have many types of actin structures, which must assemble from a common monomer pool. Yet, it remains poorly understood how monomers are distributed to and shared between different filament networks. Simplified model systems suggest that monomers are limited and heterogeneous, which alters actin network assembly through biased polymerization and internetwork competition. However, less is known about how monomers influence complex actin structures, where different networks competing for monomers overlap an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 71 publications
8
75
0
Order By: Relevance
“…Profilin-actin serves as source of actin for microfilament polymerization and as such co-operates with actin nucleation and elongation promoting proteins (26,27,28,29,33,39,40). A possible scenario is therefore that the loss of profilin results in less of actin polymerization in the centrosomal region in analogy with what was recently reported for the cell edge (41); as a consequence, less of steric hindrance (8,42) would reduce a possible space constrain for enhanced de novo microtubule nucleation. Alternatively, because actin is a structural component of functional γTuRCs (22,23,24), centrosomal profilin may tune the availability of actin for γTuRC.…”
Section: Discussionmentioning
confidence: 79%
“…Profilin-actin serves as source of actin for microfilament polymerization and as such co-operates with actin nucleation and elongation promoting proteins (26,27,28,29,33,39,40). A possible scenario is therefore that the loss of profilin results in less of actin polymerization in the centrosomal region in analogy with what was recently reported for the cell edge (41); as a consequence, less of steric hindrance (8,42) would reduce a possible space constrain for enhanced de novo microtubule nucleation. Alternatively, because actin is a structural component of functional γTuRCs (22,23,24), centrosomal profilin may tune the availability of actin for γTuRC.…”
Section: Discussionmentioning
confidence: 79%
“…Using the protein delivery assessment methods described in steps 6–8, we have shown that the amount of delivered protein is linearly proportional to the bath concentration in the electroporation reaction for FITC-labeled dextran (dextran-FITC) ( Figure 1 A), Alexa 647-labeled thymosin β4 (Tβ4-647) ( Figure 1 B), Tβ4-647 that has been co-electroporated with dextran-FITC ( Figure 1 C), and profilin 1 ( Figure 1 D) ( Skruber et al., 2020 ). Further, we have shown that proteins are functional after delivery by electroporation.…”
Section: Expected Outcomesmentioning
confidence: 98%
“…For imaging, coverslips need to be cleaned and coated with appropriate reagents to help the cells adhere to them. Below we detail coating the coverslips with laminin as in ( Skruber et al., 2020 ); however, the specific reagents (ex. fibronectin, poly-d-lysine) and incubation times/temperatures will vary depending on the cell type used.…”
Section: Before You Beginmentioning
confidence: 99%
See 2 more Smart Citations